Penambahan pigmen alami yang disalut tepung agar untuk meningkatkan kekuatan antioksidan pada tempe - Aditya Surya Piansti; Anggara Mahardika; Lusiawati Dewi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Background: Tempeh is a traditional Indonesian food that has a relatively low antioxidant activity. The addition of natural pigments is one solution to increase the antioxidant activity of tempeh. However, natural pigments are very susceptible to damage due to environmental factors, so it is necessary to coat with certain materials, such as agar powder to protect the pigments from damage. Research purposes: The aim of the study to analyze the effect of adding natural pigments coated with agar powder on the antioxidant strength of tempeh. Method: The sample used was tempeh with the addition of pigment powder uncoated and coated with 2%, 3%, 4% of agar, and tempeh without the addition of pigments as control. The antioxidant activity strength was analyzed using the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) method at fermentation time of 0 and 48 hours. Results and Discussion: The results showed that the addition of pigments and fermentation time were able to significantly increase the antioxidant strength of tempeh compared to control where the IC50 value of the control at 0 hours of fermentation was 166,45±38,58 mg/ml which changed to 69,45±3,49 mg/ml after 48 hours of fermentation. Antioxidant activity were stronger in tempeh with addition of pigment where IC50 value of tempeh with uncoated pigments, coated pigments with 2%, 3%, and 4% of agar were 23,53±5,46 mg/ml, 21,91±6,02 mg/ml, 21,53±6,03 mg/ml, and 29,69±11,04 mg/ml, respectively. Nevertheless, the antioxidant activity strength from all treatments were considered as weak (IC50>200 µg /ml). Conclusion: The addition of pigments uncoated and coated with agar powder and fermentation time were able to increase the antioxidant strength of tempeh. Coating treatment is also able to maintain the pigment color from degradation in the fermentation process.